Peran Entrepreneurship Education Terhadap Minat Berwirausaha Melalui Entrepreneurial Self-Efficacy Sebagai Mediasi - Ni Putu Candra Lestari; Ni Made Yudhaningsih; I Made Anom Arya Pering (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The object of this research is at Mahendradata University, to analyze the role of Entrepreneurship Education on Entrepreneurial Self-Efficacy as Mediation, using a quantitative methodology with a questionnaire, with a population of 109 people and a sample of 52 respondents, namely Alumni graduates of the Faculty of Economics and Business, Mahendradata University Batch 2021. Using 4 hypotheses with SEM – PLS analysis tools. The results of this study (1) Entrepreneurship Education has a positive and significant effect on the interest in entrepreneurship, (2) Entrepreneurship Education has a positive and significant effect on Entrepreneurial Self-Efficacy, (3) Entrepreneurial Self-Efficacy has no significant positive effect on entrepreneurial interest, and (4) Entrepreneurial Self-Efficacy mediates Entrepreneurship Education and has no significant positive effect on entrepreneurial interest.